The growth-employment-poverty nexus in Latin America in the 2000s: El Salvador country study - Guillermo Cruces; Gary Fields; David Jaume; Mariana Viollaz (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
During the 2000s, El Salvador experienced slow economic growth for Latin American standards. The country underwent a recession during the international crisis of 2008, but returned to pre-recession output level in 2011. Changes in labour market conditions were mixed. The unemployment rate fell, and the mix of employment by occupations, economic sector, and education improved slightly. However, the employment mix by occupational position deteriorated, and the share of registered workers and earnings decreased. Most labour indicators were affected adversely by the crisis, and some have yet to return to pre-crisis levels. Most poverty and inequality indicators fell over the period.
Keywords: O15; J01; J30; 330; El Salvador; Latin America; inclusive growth; labour market; poverty